2021
DOI: 10.3390/w13223184
|View full text |Cite
|
Sign up to set email alerts
|

Low-Calcium Cave Dripwaters in a High CO2 Environment: Formation and Development of Corrosion Cups in Postojna Cave, Slovenia

Abstract: Speleothems have proven to be one of the most reliable terrestrial archives for palaeoclimate research. However, due to the complexity of karst systems, long-term monitoring and high-resolution analyses of the cave atmosphere and water geochemistry have become essential to better constrain the factors that control calcite growth and how geochemical palaeoclimate proxies are encoded into speleothems. While calcite precipitation incorporates the palaeoclimate signals into the speleothem fabric, certain condition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The dissolution value calculated from the mean levels in the cross-section shown in Figure 6C is approximately 14 µm over 28 weeks in the summer season. Since the summer season, with highest cave air CO 2 concentrations (Kukuljan et al, 2021a), has been shown to cause the greatest amount of dissolution (Kukuljan et al, 2021b), this dissolution value encompasses the majority of the total dissolution for the whole year. Therefore, this value would represent a minimum dissolution of 14 µm yr −1 , which is consistent with typical rates of solutional denudation in karst (e.g., Ford & Williams, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissolution value calculated from the mean levels in the cross-section shown in Figure 6C is approximately 14 µm over 28 weeks in the summer season. Since the summer season, with highest cave air CO 2 concentrations (Kukuljan et al, 2021a), has been shown to cause the greatest amount of dissolution (Kukuljan et al, 2021b), this dissolution value encompasses the majority of the total dissolution for the whole year. Therefore, this value would represent a minimum dissolution of 14 µm yr −1 , which is consistent with typical rates of solutional denudation in karst (e.g., Ford & Williams, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…), Slovenia (Figure 2). Within this chamber, there are many dissolution features that have formed as cylindrical "cup shapes" below drip points (Kukuljan et al, 2021b) in the journal Water. These are thought to be forming due to the CO 2 -rich atmospheric conditions in this particular location (Johnston et al, 2019;Kukuljan et al, 2021a).…”
Section: Tablet Preparationmentioning
confidence: 99%